Cutaneous metastasis as the first manifestation of occult malignant breast neoplasia - Weimann, Ellem Tatiani de Souza (An Bras Dermatol, 2016)
Cutaneous metastases from primary internal malignancies represent 0.7-9% of patients with cancer. We report a 65-year-old female patient referred for evaluation of normochromic papules on the trunk and upper limbs that had been present for three months. A skin biopsy revealed diffuse cutaneous infiltration by small round cell tumors. Immunohistochemistry was positive for AE1/AE3, CK7, estrogen receptor and mammaglobin. The final diagnosis was cutaneous metastasis of occult breast cancer, since the solid primary tumor was not identified. The location of the primary tumor can not be determined in 5-10% of cases. In these cases, 27% are identified before the patient’s death, 57% at autopsy, and the remaining 16% can not be located.